2016
DOI: 10.1364/optica.4.000008
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-encoded photonic qubits for scalable quantum information processing

Abstract: Among the objectives toward large-scale quantum computation is the quantum interconnect: a device which uses photons to interface qubits that otherwise could not interact. However, current approaches require photons indistinguishable in frequency-a major challenge for systems experiencing different local environments or of different physical compositions altogether. Here we develop an entirely new platform which actually exploits such frequency mismatch for processing quantum information. Labeled "spectral lin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
252
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 279 publications
(253 citation statements)
references
References 83 publications
1
252
0
Order By: Relevance
“…With parallel detection with a sufficient number of detectors, multiple sidebands lying between original biphoton comb lines could be used, substantially mitigating unnecessary loss and opening the door to stronger phase modulation to construct superpositions of a larger number of frequency bins. Tailoring the rf waveform driving the phase modulator could also contribute to improving efficiency [27].…”
Section: Discussionmentioning
confidence: 99%
“…With parallel detection with a sufficient number of detectors, multiple sidebands lying between original biphoton comb lines could be used, substantially mitigating unnecessary loss and opening the door to stronger phase modulation to construct superpositions of a larger number of frequency bins. Tailoring the rf waveform driving the phase modulator could also contribute to improving efficiency [27].…”
Section: Discussionmentioning
confidence: 99%
“…For example, optical filters and/or low temperatures are required to remove background noise due to powerful optical pumps, either from the sources themselves or Raman scattering in the nonlinear medium. And achieving the necessary nonlinear mixing for arbitrary combinations of modes will require additional pump fields, as well as properly engineered phase-matching conditions.Recently we proposed a fundamentally distinct platform for frequency-bin manipulations, relying on electrooptic phase modulation and Fourier-transform pulse shaping for universal QIP [12]. Our approach requires no optical pump fields, is readily parallelized, and scales well with the number of modes.…”
mentioning
confidence: 99%
“…Combined with its native parallelizability and absence of optical noise sources, our mixer design offers new opportunities for a range of quantum information applications, including linearoptical computation [12], quantum repeaters [13], and quantum walks [14]. The tritter also serves as an elementary building block for a frequency version of three-mode directionally unbiased linear-optical multiports, which find application in quantum simulations [15] and Bell state discriminators [16].Background.-The Hilbert space of interest consists of a comb of equispaced frequency bins, with operatorsĂą n (n ∈ Z) that annihilate a single photon in the narrowband modes centered at frequencies ω n = ω 0 + n∆ω [12,17]. A qudit is represented by a single photon spread over d such modes, and the objective is to implement a frequency multiport V connecting the inputĂą (in) n and outputĂą (out) m modes in some desired fashion:Ăą…”
mentioning
confidence: 99%
“…As the modulator is embedded in a single-mode fiber, all of the frequency components are in the same spatial mode. This allows transferring such qubit states over a long distance using fiber optic networks without the problems that characterize polarization qubits [14]. Through HOM measurements, we have demonstrated that the indistinguishability of a stream of individual photons emitted by a QD is fully preserved in the presence of additional frequency sidebands generated via a phase modulator for a range of modulation frequencies.…”
Section: Fig 2 (A)mentioning
confidence: 98%
“…Frequency qubits can be generated through phase modulation of a single photon [14,16], where the information is encoded in the relative amplitude between the sidebands. Recently, Lukens and Lougovski proposed a universal linearoptical quantum computing (LOQC) platform using frequency components generated from an electro-optic modulators [14]. Similarly, there has been proof-of-concept demonstrations of the 1984 protocol of Bennett and Brassard (BB84) using phase-modulated weak coherent sources [13,17].…”
mentioning
confidence: 99%